Petrocodon ferrugineus (Gesneriaceae), a new species from Guangxi, China - Wei, Yi-Gang (2007)
A new species, Petrocodon ferrugineus Y. G. Wei (Gesneriaceae) from Guangxi province in southern China, is described and illustrated. Its relationship with Petrocodon dealbatus Hance is discusse. The new species is distinguished by the dense villous pubescence of the leaves, bracts, and plant axes; filaments that are linear, glabrous, curved, and somewhat expanded in the middle; and fruits with 4-loculicidal, but not septicidally dehiscent, capsules.
il byn
Keywords: Gesneriaceae; Petrocodon